Investigating Soil Instability and Subsidence Risks Using an Integrated ERT and MASW Analysis - Oboshenure, K. K.; George, Godwin C; Keme, P. (European Journal of Applied Sciences, 2024)
Subsidence is a major structural concern, particularly in deltaic areas with soft, compressible soils. This study looks into the subsurface conditions at Niger Delta University, Amassoma, using a combination of Electrical Resistivity Tomography (ERT), Multichannel Analysis of Surface Waves (MASW), and Standard Penetration Tests. Analysis of five ERT profiles identified three stratigraphic layers having resistivity values that ranged from 0.453 Ωm to 145 Ωm, indicating different soil compositions and moisture levels. MASW measurements also confirmed these findings, with shear wave velocities ranging from 207 m/s in the topmost layer characterised with moisture to 824 m/s in the deepest probed layer. The computed Standard Penetration Test (N-value) findings revealed a significant variance in soil strength, with N-values ranging from 8.3 in the topmost layer to 459 in the deepest layer probed. This complex profile suggests that the softer upper layer, which is insufficiently secure for normal foundations, overlies stiffer layers. The study emphasises the importance of deep foundation techniques and soil stabilisation in reducing subsidence risks and ensuring the structural integrity of facilities. These findings provide critical insights into geotechnical engineering techniques in deltaic regions, emphasising the significance of thorough subsurface investigations in anticipating and dealing with structural stability issues.